ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISSEMINATION PERUSAHAAN DI MEDIA SOSIAL - Hidayat, Ramdhon (2020)
Social media as a channel for financial dissemination has changed the way corporate information. The article analyzes the factors that influence the spread of financial dissemenation on social media. The data comes from 240 companies listed on the Indonesia Stock Exchange in 2019. The results of the study have a significance level of 5%, indicating that if Indonesia, market capitalization has a significant influence on financial dissemination activities through social media. Leverage have insignificant effects with respect to financial dissemenation of accounting through social media.